Analisis Dampak Kerjasama Indonesia-China dalam program program OBOR (One Belt Road Initiative) dalam perspektif Liberalisme - Napitupulu, Harley Kevin Philip; Rifai, Maulana; Marsingga, , Prilla (Jurnal Ilmiah Wahana Pendidikan, 2024)
The OBOR (One Belt One Road) project is one of the ambitious steps taken by China in an effort to revitalize the silk road. The OBOR Project seeks to build global connectivity by building land and sea trade routes that will connect China with various countries in Asia, Europe and Africa. One of the countries involved in cooperation with China in the OBOR Project is Indonesia. This cooperation literally has a fairly positive impact on Indonesia's development, but there are some views that are quite sentimental in viewing this OBOR cooperation, so in this study, the author will use a qualitative method and apply the perspective of Liberalism to see the threats and potential of OBOR cooperation between China and Indonesia.